Utilization of Google Translate in Teaching Writing Skills for Students of STAI Masjid Syuhada - Hafidhah, Shiddiqoh; Elmi, Bellah Asa O'Neal; Syamsiyah, Dailatus; Astuti, Widi (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2025)
This study aims to explore the response of STAI Masjid Syuhada students to the use of Google Translate in learning maharah kitabah. This study uses a descriptive qualitative approach. This approach aims to understand phenomena based on the experiences, perceptions, and views of the research subjects. The subject of this research is STAI students of the Syuhada Masjid. This sampling technique is purposive sampling. The selection of subjects is based on specific criteria relevant to the research objectives: students actively participating in imla' and insya' courses and using Google Translate for learning maharah kitabah. The data collection technique used in this study is a closed questionnaire. The results of the study show that most students often use Google Translate, especially in learning maharah kitabah. The reasons why students use Google Translate are quite varied, including to complete assignments, understand vocabulary, improve grammar, and improve the quality of writing. However, with Google Translate, the majority of students feel helped in learning maharah kitabah. This study suggests using Google Translate as a learning tool, but it still requires double-checking to ensure optimal use.